Characteristic Functions and Borel Exceptional Values of E-Valued Meromorphic Functions - Zhaojun Wu; Zuxing Xuan (Abstract and Applied Analysis)
The main purpose of this paper is to investigate the characteristic functions and Borel exceptional values of E-valued meromorphic functions from the ℂR={z:|z|<R},   0<R≤+∞ to an infinite-dimensional complex Banach space E with a Schauder basis. Results obtained extend the relative results by Xuan, Wu and Yang, Bhoosnurmath, and Pujari.